Problematika Pendidikan Islam Anak Usia Dini Di Era Digital: Tantangan Dan Solusi Untuk Pengembangan Karakter - Trismayanti, Euis (STAI Darul Qalam Tangerang, 2024)
This qualitative case study examines the problems of early childhood Islamic character education in the digital era. Adopting Bandura's Social Learning Theory[1] and Bronfenbrenner's Ecological System[2], the study identified key challenges such as exposure to easily replicable negative content, screen time management difficulties, limited supervision, and value conflicts due to digital penetration in children's microsystems. The solutions identified include active parental mentoring, institutional strategies for Islamic PAUD, curation of Islamic digital content, strengthening direct interaction and habituation of values, and collaboration between home and school.